Rothia dentocariosa Endocarditis in an Unsuspecting Host: A Case Report and Literature Review - Stacy Willner; Zaid Imam; Ismail Hader (Case Reports in Cardiology)
Rothia dentocariosa, a gram-positive coccobacillus, is a commensal bacterium that is part of the oropharynx and respiratory tract. In the past, it was known to be a cause for periodontal disease, but in recent years, Rothia dentocariosa has been found to be the cause of several other infectious entities, of which endocarditis is the most predominant. We present the case of a healthy 62-year-old female who, after undergoing routine dental cleaning two months prior, developed subacute bacterial endocarditis of the mitral valve, with subsequent cerebral septic emboli causing an occipital hemorrhagic cerebrovascular accident, all secondary to Rothia dentocariosa.